Pengaruh Modernitas Individu dan Pemanfaatan Teknologi Informasi terhadap Minat Berwirausaha Generasi Z Pada Siswa SMA di Kota Malang - Fariha Nuraini; Wahjoedi Wahjoedi (Jurnal Pendidikan Ekonomi, 2023)
Generation Z is a generation that has the potential to become successful entrepreneurs in the future. Generation Z, which is in the birth range from 1995-2010, has innovative ideas to create modern business opportunities. Self-confidence and the discovery of new things are elements of individual modernity that build Generation Z's interest in entrepreneurship. Generation Z who are recovering in the digitalization era can take advantage of information technology to start entrepreneurship. This study aims to find out how individual modernity and the use of information technology affect Generation Z's interest in entrepreneurship partially and simultaneously. 294 high school students in Malang City including SMAN 1 Malang, Brawijaya Smart School Malang High School, Panjura High School, and UM Laboratory High School who were the subjects of this study were given questionnaires using a quantitative descriptive research approach. The research findings reveal a significant positive effect, both partially and simultaneously on individual modernity variables (X1) and information technology utilization (X2) on the interest in entrepreneurship of Generation Z (Y). The results of this study indicate that acquisition, acceptance of new things, and self-confidence encourage Generation Z's interest in entrepreneurship. The use of information technology also encourages interest in entrepreneurship for Generation Z by looking for things related to entrepreneurship. Generation Z's interest in entrepreneurship will not just end up as a desire if there is awareness from within them to realize business opportunities in real life.